2004
DOI: 10.1016/s0736-0266(03)00128-1
|View full text |Cite
|
Sign up to set email alerts
|

Strength and voluntary activation of the quadriceps femoris muscle at different severities of osteoarthritic knee joint damage

Abstract: Objective: Improvements of quadriceps motor deficits represent a major therapeutical target in knee osteoarthritis (OA). In the present study, we investigated changes in quadriceps function at different stages of osteoarthritic cartilage damage.A4ethod.s: Measurements of quadriceps voluntary activation (VA) and maximum voluntary contraction (MVC) were performed by a twitch interpolation technique and the total muscular capacity (TMC) was calculated as the ratio of MVC and VA. We assessed 68 patients (56.7 2 9.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

5
58
2
3

Year Published

2006
2006
2013
2013

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 63 publications
(68 citation statements)
references
References 42 publications
5
58
2
3
Order By: Relevance
“…It has been reported that knee OA patients have a 14% to 45% reduction in quadriceps strength compared to control subjects. 6,8,18,19,21 In the present study, torque reductions were 37% and 38% for dorsiflexion and plantar flexion, respectively. This torque reduction might be caused, at least in part, by arthrogenous muscle inhibition, 13,35 and by a loss Figure 1.…”
Section: Discussionsupporting
confidence: 45%
See 1 more Smart Citation
“…It has been reported that knee OA patients have a 14% to 45% reduction in quadriceps strength compared to control subjects. 6,8,18,19,21 In the present study, torque reductions were 37% and 38% for dorsiflexion and plantar flexion, respectively. This torque reduction might be caused, at least in part, by arthrogenous muscle inhibition, 13,35 and by a loss Figure 1.…”
Section: Discussionsupporting
confidence: 45%
“…6,8,[15][16][17][18][19][20][21] It has been shown that in knee OA the quadriceps strength is usually reduced by 14% to 45% compared to control subjects. 6,8,18,19,21 Sirca et al 22 reported that degenerative hip OA was associated with an atrophy of type II fibers. Nakamura and Suzuki 17 also reported selective type II fiber atrophy in hip and knee OA.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies on muscle pathology in conjunction with OA focus on the hip and knee and on muscle force measurements. It has been shown that in knee OA the quadriceps strength is usually reduced by 14-45 % compared to control subjects [17][18][19]. Sirca et al reported that OA of the hip was strongly associated with a type II fiber atrophy of the gluteal muscles [18].…”
Section: Discussionmentioning
confidence: 99%
“…6,7,17,19,25,26 Quadriceps activation failure is a complex issue, due to the variety of factors and mechanisms that likely contribute to its existence. The inability to optimally activate the quadriceps muscle may be modulated by both cortical 8 and spinal reflex mechanisms.…”
mentioning
confidence: 99%